2017
DOI: 10.3892/or.2017.5998
|View full text |Cite
|
Sign up to set email alerts
|

SP1 promotes tumor angiogenesis and invasion by activating VEGF expression in an acquired trastuzumab-resistant ovarian cancer model

Abstract: Ovarian cancer is one of the most common gynecologic cancers and the leading cause of mortality in women worldwide. HER2/neu is overexpressed in various types of cancers and is most commonly associated with decreased survival. Trastuzumab is a humanized anti-HER2 monoclonal antibody for the treatment of HER2-positive breast cancers. However, primary and/or acquired resistance occurs in up to 62% patients during the first year of treatment. Vascular endothelial growth factor (VEGF) is a well-known angiogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 24 publications
(33 reference statements)
2
21
0
Order By: Relevance
“…SP1 affects the growth and metastasis of tumors by regulating the expressions of tumor‐related genes . It can bind to specific sites on the promoter of vascular endothelial growth factor (VEGF) or VEGF receptor, which further promotes the progress of tumors . SP1‐regulated tumor‐related genes are involved in a variety of cell functions, including cell cycle (Cyclin D1, TGF‐α, E2F1), apoptosis (Bax, Bcl2), tumor metastasis (TGF‐β, MMP2) and angiogenesis (VEGF) .…”
Section: Discussionmentioning
confidence: 71%
“…SP1 affects the growth and metastasis of tumors by regulating the expressions of tumor‐related genes . It can bind to specific sites on the promoter of vascular endothelial growth factor (VEGF) or VEGF receptor, which further promotes the progress of tumors . SP1‐regulated tumor‐related genes are involved in a variety of cell functions, including cell cycle (Cyclin D1, TGF‐α, E2F1), apoptosis (Bax, Bcl2), tumor metastasis (TGF‐β, MMP2) and angiogenesis (VEGF) .…”
Section: Discussionmentioning
confidence: 71%
“…The cross‐talk between the cancer cells and their environment involves numerous oncogenic transcription factors. These factors are aberrantly reactivated and trigger a series of cellular events such as genome instability, reprogrammed metabolism, infinite proliferation, angiogenesis, invasion and metastasis, immune cell infiltration, and enhanced inflammation, all of which have been widely recognized as the characteristics of cancer …”
Section: Introductionmentioning
confidence: 99%
“…For example, SP1 was overexpression in breast cancer and could regulate TINCR- MIR - 7 -KLF4 axis, which in turn stimulate cell proliferation but suppress cell apoptosis [ 7 ]. In ovarian cancer, upregulation of SP1 enhanced VEGF expression and resulted in angiogenesis and migration stimulation in vitro and in vivo [ 8 ]. Another study investigated the role of SP1 in hepatocellular carcinoma demonstrated that SP1 regulate cystathionine γ-lyase gene expression in human hepatocellular carcinoma cell lines to promote cell proliferation and cell cycle progression [ 9 ].…”
Section: Introductionmentioning
confidence: 99%